Working with traumatized youth in child welfare - Webb, Nancy Boyd, 1932- (Social work practice with children and families., 2006)
Until recently, there has not been a great deal of overlap in the child welfare and trauma literatures. This text bridges that divide by integrating perspectives from both fields to help practitioners understand and address the special needs of maltreated children and adolescents and their families. Current knowledge on attachment, trauma, and risk and resilience is clearly explained, including the impact of abuse on the brain. Readers learn how to conduct assessments and implement a range of effective helping strategies with youth in foster care and other settings. Featuring extensive ca.